2010
DOI: 10.1590/s0100-29452010000400014
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição de óleos ao acaricida cyhexatin sobre o ácaro Brevipalpus phoenicis e na retenção de calda por folhas de citros

Abstract: , NATALI CALAZANÇA DOS SANTOS 4 RESUMO-A adição de óleos à calda de pulverização, muitas vezes, é utilizada a campo sem o adequado conhecimento sobre a absorção do produto fitossanitário pelo alvo, retenção de calda e até mesmo sobre a praga e a cultura. O objetivo do trabalho foi avaliar o efeito da adição de óleos ao acaricida cyhexatin sobre o ácaro Brevipalpus phoenicis e na retenção de calda por folhas de citros. Avaliou-se a mortalidade de ácaros, utilizando-se de frutos de laranja com uma arena circunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…This effect of the adjuvants is consistent with the results reported by other authors for other adjuvants (ANDRADE et al, 2010;SOARES et al, 2013).…”
Section: Deposit Quantity As a Function Of Different Spraying Liquidssupporting
confidence: 92%
“…This effect of the adjuvants is consistent with the results reported by other authors for other adjuvants (ANDRADE et al, 2010;SOARES et al, 2013).…”
Section: Deposit Quantity As a Function Of Different Spraying Liquidssupporting
confidence: 92%
“…These results imply that a greater spreading factor on the surface due to lower surface tension resulted in a greater spreading of the droplets and therefore enabled reduction of the solution volume (MATUO et al 1989). The solution with glyphosate has a diminution the reduction in surface tension when vegetable oil and mixture tributyl citrate + polydimethylsiloxane were added, except at 180 seconds (Figure 1 With a greater spreading factor, can occur a reduction of the maximum quantity of liquid retained by the leaves, as showed in the research of ANDRADE et al (2010), where was observed that the addition of oil, either mineral or vegetable, to an acaricide in the spraying solution reduced the maximum quantity of liquid retained by the leaves of citrus plants, which suggested the possibility of reducing the amount of solution needed for good coverage of the plant. MACIEL et al (2010) also reported that mineral oil proved effective in reducing the surface tension for tank mixing with glyphosate formulations and with chlorimuron-ethyl.…”
Section: Surface Tension and Contact Angle On The Leaves Of Ipomoea Hmentioning
confidence: 84%
“…Besides these aspects, the addition of vegetable oil to agricultural spray mixes is also a routine with recognized efficacy and less potential for phytotoxicity when compared to mineral oils (Mendonça et al 2007, Andrade et al 2010.…”
Section: Effectiveness In the Fieldmentioning
confidence: 99%